The split Arab/Jew figure revisited. (14th March 2020) - Shohat, Ella
ABSTRACT: In this essay, Shohat argues that the question of the Arab-Jew, in contrast to present-day ethnonationalist common sense, must be rearticulated as mutually constitutive categories, so as to address the complex imaginaries of both 'the Arab' and 'the Jew'. Elaborating on her earlier dialogue with Edward Said's account of the bifurcated Oriental/Semitic myth—one rendered as the Orientalist (the Jew) and the other as the Oriental (the Arab)—Shohat offers a genealogical reading of this gradual splitting, locating it prior to the partition of Palestine and even to the emergence of Zionism, and tracing it back to the dissemination of a colonial-inflected Enlightenment discourse. More crucially, Shohat asks where the indigenous Jew of 'the Orient', and more specifically the Arab-Jew, might fit conceptually within this split. Today, with the epic-scale reconceptualization of belonging in the wake of partition, diasporization and competing nationalist imaginaries, the Arab-Jew figure silently occupies an ambiguous position within the bifurcation. Yet a critical analysis of the Orientalist splitting that sidesteps the question of the Arab-Jew risks reproducing the fixed ethnonationalist lexicon that posits Jewishness and Arabness as irreconcilable. At the same time, this very ambiguity, Shohat argues, was already fomented with the imperial 'translation' of the Enlightenment project into a racialized idiom, now applied differentially to the Muslim and the Jew-within-the-Orient. This essay traces such representational ruptures back to the nineteenth century, examining various instances of what the essay regards as 'the de-indigenization of the Arab-Jew'. To illustrate her thesis, Shohat examines the gendered imagining of both Jewish and Muslim communities within a relational and transnational comparative framework. Orientalist tropes such as the odalisque, the hammam and the un/veiled female had long been projected on to Muslim and Jewish women throughout the region but, with the emergence of imperial 'minorities' discourse, the exoticized Jew-in-the-Orient became the object of a gendered rescue phantasy, as vividly illustrated in Dehodencq's painting L'Exécution de la juive. Rather than a document of Muslim antisemitism, however, the colonial visual archive inadvertently registers what Shohat defines as a 'split-within-the split', highlighting the novel formation of an ambivalent indigeneity for Arab-Jews within 'the Orient'. Yet the aesthetic dispositions also inadvertently and paradoxically reveal an underlying, thoroughly syncretic and shared Judaeo-Muslim cultural geography. Here the pivotal figure of the Arab-Jew reveals an intricate landscape of belonging that offers an alternative conceptual framework in which to discuss the ruptures prior to the grand rupture of partition, and to illuminate the post/colonial transformation that dramatically impacted the narrative of Jewish at-homeness within Muslim spaces.